Fishery Product Consumption Rate in Bintan Pesisir District, Bintan Regency - Adrinal, Adrinal; Nevrita, Nevrita; Apdilah, Dony (Jurnal Perikanan dan Kelautan, 2021)
Bintan Regency currently consists of 272 large and small islands. The Bintan Pesisir District was formed based on the Bintan Regency Regional Regulation Number 12 of 2007. The preparation of this scientific article was carried out in April 2021 in the Bintan Pesisir District, especially the Kelong, Numbing, Mapur and Air Glubi villages using descriptive analysis based on a literature review using secondary data as a source of information. The consumption rate of fishery products in the Bintan Pesisir District has increased every year. In 2017 the volume of fishery production in the coastal Bintan District produced 7,587.27 tons, in 2018 it was 7,753.88 tons and while in 2019 the Bintan Pesisir District produced 7,884.60 tons